Use of a hip spica for management of an acetabular labral tear in a female collegiate gymnast: a case report - Greenwood, A.; Giblin, N. A.; Gillette, C. (International Journal of Athletic Therapy & Training, 2020)
The patient was a 20-year-old female gymnast complaining of lateral hip pain, posterior to the greater trochanter, that increased with hip extension and external rotation. Over the course of 1 month during the season, pain progressively shifted to the groin and hip extension and external rotation became limited. A minimally painful exercise program was implemented in conjunction with a supportive hip spica, assisting extension and external rotation while limiting flexion and internal rotation during therapeutic exercise. The resulting implementation of a hip spica is a novel way to reduce pain and improve function to augment current conservative treatments.